Question about Texas Instruments TI-84 Plus Calculator

1 Answer

Solving matrix -3x+4y+5z = 7 4x+3y+2z = 9 -5x+5y+3z = -10

Posted by robenim on

  • Anonymous Mar 13, 2014

    What is the y-intercept from line -3x-4y=15



1 Answer


  • Level 1:

    An expert who has achieved level 1.


    An expert whose answer got voted for 2 times.

  • Contributor
  • 3 Answers

Go to your matrix button and enter a "3x4" matrix.

Then enter it as follows:

-3 4 5 7
4 3 2 9
-5 5 3 -10

Then exit out and go to "2nd->matrix->math->rref(". Then press enter.

Your screen should look like this:


Then go to matrix and select your 3x4 matrix, press enter and close it with a parathesis. Your screen should look like this:


Press enter and the screen should say this:

1 0 0 2
0 1 0 -3
0 0 1 5


Hope this cleared up the confusion!


Posted on Mar 14, 2009


Add Your Answer


Uploading: 0%


Complete. Click "Add" to insert your video. Add



Related Questions:

1 Answer

8x + 3y = 3 4x + 5y = -23

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23
Solving the first one for x:
8x = -23-3y
x = -23/8 - 3/8y
Substituting this value for x into the second equation:
34(-23/8 - 3/8y) + 5y = -23
-97.75 - (34)(.375)y + 5y = -23
-97.75 - 12.75y + 5y = -23
-97.75 -7.75y = -23
-7.75y = 97.75-23=74.75
y = -74.75/7.75 = -9.645161
Substitution back into the equation for x:
x = -23/8 - 3/8(-9.645161)
x = -2.875 + 3.616935
x =.741935

Dec 12, 2014 | Bagatrix Algebra Solved! 2005 (105101) for...

1 Answer

Find the equations of circles passing through (1,-1),touching the lines 4x+3y+5=0 and 3x-4y-10=0

First, I graphed the lines and the point using

I noticed that the two lines are perpendicular to each other and the point (1,-1) appears to be on the right side of the circle, on a line parallel to 3x -4y-10=0. The equation of this line is y= 3/4x - 1.75. The y-intercept is -1.75. Now we have two points on the opposite sides of the circle, (1, -1) and (0,-1.75). The midpoint formula will give you the centre of the circle and the distance formula will provide the radius.

Let me know if you have any questions.

Good luck.

Desmos Beautiful Free Math

Jun 09, 2014 | Office Equipment & Supplies

1 Answer

Problems matrix

This is no linear system. You cannot solve it like that using the matrix techniques. Haven't you made a mistake in writing the equations?
If that is tryly the system you want to solve, I suggest that you make a change of variables as follows:
X=1/x , Y= 1/y, Z=1/z (it being understood that x, y, z cannot be equal to 0). You will have to exclude the values x=0, y=0, z=0
Not I am not being sloppy, X and x are different entities, same with Y and y, Z and z.
Your system becomes

Now that is a linear system. Solve it using matrices or Cramer's rule, When you obtain X, Y, and Z, get x=1/X, y=1/y, z=1/Z
The actual implementation of the solution method will depend on the exact model of calculator you are using. Not knowing that, I cannot advise you how to do it.

If I have not made any mistakes, the results are X=-58/9,Y=106/9, Z=-32/9. And x, y, z are just the reciprocals of their namesake.

Dec 13, 2013 | Office Equipment & Supplies

1 Answer

If y=f(x)=5x+3/4x-5 , show that x=f(y)

Write the equality in the form y=(5X+3)/(4X-5). Insert parentheses to ensure a correct result.
  1. Multiply both sides of the equality by (4X-5). This gives (4X-5)y=(5X+3).
  2. Open the parentheses as 4Xy-5y=5X+3
  3. Subtract 5X from both sides 4Xy-5y-5X=5X-5X+3
  4. Add 5y to both sides 4Xy-5X-5y+5y=5y+3 or 4Xy-5X=5y+3
  5. Factor the X on the left side X(4y-5)=5y+3
  6. If 4y-5 does not vanish, you can isolate X by dividing both members of the equality by (4y-5).
  7. You get X=(5y+3)/(4y-5)=f(y)
Compare the initial function f(x) and the function just found: They have the same form: X and y have switched places.

Jun 24, 2012 | Mathsoft StudyWorks! Mathematics Deluxe...

1 Answer

2x -y +z -w = -1 x +3y -2z = -5 3x -2y +4w = 1 -x +y -3z -w = -6 solve for the variables w,x,y,z using matrix equation

You have to put the equations into matrix form first. To do this, each variable has one column in the first matrix and you fill in the co-efficients for the variables. The second matrix has one column and contains all the numbers.

{ 2 -1 1 -1} = Matrix A
{ 1 3 -2 0}
{ 3 -2 0 4}
{-1 -3 -3 -1}

{-1} = Matrix B
{ 1}

{x=-2} = A*(B^-1)

I used excel for all my calculation and a helpful tutorial can be found here. I hope this helps and have a nice day!

May 05, 2011 | Computers & Internet

1 Answer

4x-y-2z=-7 -4x+8y+5z=46 8x-3y+z=13

Type solve(exp1 and exp2 and exp3, {x,y,z})
See cap images

Dec 15, 2010 | Texas Instruments TI-89 Calculator

1 Answer

Sum to n terms of the series 1+5+12+22..........

You did not provide a general (n) term. However, I figured it to be something involving n^2. Hence the sum to n terms can be of the form: xn^3 + yn^2 + zn. Using the partial sums: 1, 6 (1+5), and 18 (1+5+12) we can build a linear equations system:
1= x + y +z (n=1)
6 = 8x + 4y +2z (n=2, n^2=4, n^3 = 8)
18 = 27x + 9y + 3z (n=3, n^=9, n^=27)
Solving for x,y,z we get x = 1/2, y= 1/2, z =0
Hence 1+5+12+22+..+ f(n^2)= 1/2(n^3+n^2)

Nov 04, 2010 | Refrigerators

2 Answers

How do I solve x and y in the following equations? 5x+3y=6 2x-4y=5 Thank you

You can solve it with following method.

5x+3y=6 2x-4y=5
So 5x=6-3y so 2[(6-3y)/5]-4y=5
So x=(6-3y)/5 so 12-6y-20y=25
so -26y=25-12
so -26y=13
so y= -(1/2)
so 2x=5+4y
so 2x=5+4(-1/2)
so 2x=(10-4)/2
so 2x=6/4
so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.
Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

2 Answers

Algebra college

Consider the following system of 3 equations in 3 unknowns:
x + y = 2
2x + 3y + z = 4
x + 2y + 2z = 6Our goal is to transform this system into an equivalent system from which it is easy to find the solutions. We now do this step by step.
  • Subtract 2*(Row1) from Row2 and place the result in the second row; subtract Row1 from Row2 and place in the third row. Leave Row1 as is.
x + y = 2
y + z = 0
y + 2z = 4
  • Subtract Row2 from Row3, and place the result in row3. Leave Row1 and Row2 as they are.
    x + y = 2
    y + z = 0
    z = 4 From the last form of the system we can deduce the following unique solution to the system:
z = 4, y = -4, and x = 2-(-4) = 6Equivalently, we say that the unique solution to this system is (x, y, z) = (6, -4, 4).

Sep 17, 2008 | Belkin (F5D7230-4) Router (587009)

Not finding what you are looking for?
Texas Instruments TI-84 Plus Calculator Logo

Related Topics:

621 people viewed this question

Ask a Question

Usually answered in minutes!

Top Texas Instruments Office Equipment & Supplies Experts


Level 3 Expert

8091 Answers

Paul Bade

Level 3 Expert

1666 Answers

Tareq Bin Mostaq...
Tareq Bin Mostaq...

Level 3 Expert

1449 Answers

Are you a Texas Instruments Office Equipment and Supply Expert? Answer questions, earn points and help others

Answer questions

Manuals & User Guides